Comparison of femoropopliteal artery stents under axial and radial compression, axial tension, bending, and torsion deformations. (November 2017) - Maleckis, Kaspars; Deegan, Paul; Poulson, William; Sievers, Cole; Desyatova, Anastasia; MacTaggart, Jason; Kamenskiy, Alexey
Abstract: High failure rates of Peripheral Arterial Disease (PAD) stenting appear to be associated with the inability of certain stent designs to accommodate severe biomechanical environment of the femoropopliteal artery (FPA) that bends, twists, and axially compresses during limb flexion. Twelve Nitinol stents (Absolute Pro, Supera, Lifestent, Innova, Zilver, Smart Control, Smart Flex, EverFlex, Viabahn, Tigris, Misago, and Complete SE) were quasi-statically tested under bench-top axial and radial compression, axial tension, bending, and torsional deformations. Stents were compared in terms of force-strain behavior, stiffness, and geometrical shape under each deformation mode. Tigris was the least stiff stent under axial compression (6.6 N/m axial stiffness) and bending (0.1 N/m) deformations, while Smart Control was the stiffest (575.3 N/m and 105.4 N/m, respectively). Under radial compression Complete SE was the stiffest (892.8 N/m), while Smart Control had the lowest radial stiffness (211.0 N/m). Viabahn and Supera had the lowest and highest torsional stiffness (2.2 μN m/° and 959.2 μN m/°), respectively. None of the 12 PAD stents demonstrated superior characteristics under all deformation modes and many experienced global buckling and diameter pinching. Though it is yet to be determined which of these deformation modes might have greater clinical impact, results of the current analysis may help guide development of new stents with improved mechanical characteristics.